Regional development plan for the Caribbean 2013-2016 (Universal Postal Union BerneCH, 2013)
Focuses on a regional development plan (RDP) that supports the developing countries of the Caribbean region and will permit the mobilisation of the required financial resources and skills within a structured framework.
Keywords: POSTAL SERVICES